The association between life satisfaction, vitality, self-rated health, and risk of cancer - Folker, Anna Paldam; Hegelund, Emilie Rune; Mortensen, Erik Lykke; Wimmelmann, Cathrine Lawaetz; Flensborg-Madsen, Trine (Quality of life research, 2019)
Purpose Only few prospective studies have been conducted on the contribution of quality of life-related factors to the risk of cancer. The aim of this study was to investigate the prospective associations of three quality of life-related factors with the risk of cancer; life satisfaction, vitality, and self-rated health. Methods In 2009–2011, 7189 participants in the Copenhagen Aging and Midlife Biobank were asked to rate their life satisfaction, their vitality, and their health. The study population was followed until the end of 2015 for registration of cancer in the Danish National Patient Register. Results During the follow-up period, cancer was diagnosed in 312 individuals. Life satisfaction was not associated with the risk of cancer. Vitality was significantly associated with the risk of cancer, but the association became non-significant after adjustment for age, sex, socioeconomic position, and lifestyle factors. However, when additionally adjusting for life satisfaction, individuals who rated their vitality as low had a hazard ratio of 1.46 (95% confidence interval [CI] 1.04–2.07) for the development of cancer. Individuals who rated their health as poor had a hazard ratio of 1.70 (95% CI 1.27–2.26) for the development of cancer, compared with individuals with good, very good, or excellent self-rated health. The association remained significant after adjustment for basic confounders, life satisfaction, and vitality. Conclusion A better grasp of the significance of quality of life-related factors for the risk of cancer may be of great importance to population-based cancer prevention that aims to target early risk factors for development of cancer across widespread cancer sites.